STRATEGI PENGGUNAAN MEDIA INTERAKTIF UNTUK MEWUJUDKAN KELAS MODERN YANG EFEKTIF DI SMKN 7 BONE - Elvira Ayudhia; Hamka; Muh. Tang Rustan; Kasmiati; Fatmasari; Andi Suci Damayanti; Dwi Meilani; Muh. Akbar Al Farisi; Dian Lestari; Annisa Septiani; Riska Sari; Sri Tika Syandi; Iksan; Sherly Tri Amanda; Aliyastuti; Muh. Nur Amin Azis; Siti Andriany; Agustina Amirah; Syadelia Saufika; Nurafiah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the strategies for using interactive media in creating effective modern classrooms at SMKN 7 Bone. The development of digital technology in education requires teachers to utilize innovative learning media in order to make the teaching and learning process more interesting, active, and efficient. Interactive media are considered capable of increasing students’ learning motivation, participation, and facilitating the understanding of learning materials. This study employed a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The research subjects consisted of teachers and students at SMKN 7 Bone. The results showed that the strategies for using interactive media were implemented through the utilization of digital learning applications, multimedia presentations, educational videos, and online platforms that support student collaboration. The implementation of interactive media had a positive impact on learning effectiveness, such as increasing students’ interest in learning, involvement in the learning process, and creating a more modern and communicative classroom atmosphere. However, several obstacles were found in its implementation, including limited technological facilities, internet network constraints, and teachers’ ability to operate digital media. Therefore, support in terms of infrastructure and teacher training is needed so that the use of interactive media can be implemented optimally in creating effective modern classrooms.